Insight into a single-chamber air-cathode microbial fuel cell for nitrate removal and ecological roles - Jin, Xiaojun; Yang, Nuan; Xu, Dake; Song, Cheng; Liu, Hong (Frontiers in Bioengineering and Biotechnology, 2024)
Bioelectrochemical systems is a sustainable and potential technology in wastewater treatment for nitrogen removal. The present study fabricated an air-cathode denitrifying microbial fuel cell (DNMFC) with modular revisable and investigated the metabolic processes using nutrients together with the spatiotemporal distribution characteristics of the dominated microorganisms. Based on the detection of organics and solvable nitrogen concentrations as well as electron generations in DNMFCs under different conditions, the distribution pattern of nutrients could be quantified. By calculation it is found that heterotrophic denitrification performed in DNMFC using 56.6% COD decreased the coulombic efficiency from 38.0% to 16.5% at a COD/NO3 --N ratio of 7. Furthermore, biological denitrification removed 92.3% nitrate, while the residual was reduced via electrochemical denitrification in the cathode. Correspondingly, nitrate as the electron acceptor consumed 16.7% of the all generated electrons and the residual electrons were accepted by oxygen. Microbial community analysis revealed that the bifunctional bacteria of electroactive denitrifying bacteria distributed all over the reactor determined the DNMFC performance; meanwhile, electroactive bacteria was mainly distributed in the anode biofilm, anaerobic denitrifying bacteria was adhered to the wall, and facultative anaerobic denitrifying bacteria was distributed in the wall and cathode. Characterizing the contribution of specific microorganisms in DNMFC comprehensively revealed the significant role of electroactive denitrifying bacteria and their cooperative relationship with other functional bacteria.